Pengaruh Tanaman Pada Dataran Banjir Terhadap Kekasaran Hidrolik Sungai Barabai - Fitriani Hayati; Mohammad Yanuar Jarwadi Purwanto; Hidayat Pawitan; Suria Darma Tarigan; Latief Mahir Rachman (Jurnal Keteknikan Pertanian, 2017)
AbstractHydraulic roughness value is a value that describes the estimation of retention towards water flow due to energy loss caused by friction between channel and water. The type, density and height of vegetation cause variations in the hydraulic roughness value. The hydraulic roughness value can be observed by using a physical model representing the real condition. The objective of this research is to figure out theeffect of plants planted in floodplain by conducting a research using physical model in a laboratory. This research was conducted by carrying out experiments and observations in a laboratory on a physical model that represents the condition of the cross section of Barabai River in South Kalimantan. The model was designed with a scale of 1:110, and in the floodplain were planted bamboo plants with a space of 1.82 by 1.82 cm. The plants’ diameter and length were 0.1 cm and 8 cm, respectively. The model was made in two types, namely a model with monocrops and another model with clump. The model is combined with an open channel along with its device. The research results show that there was an effect of plants on the hydraulic roughness value. This value was indicated by n4 value which increased by 65.13% if the plants were changed from monocrops into clump. This increase was caused by the increase of plants density. Besides, it was also discovered that the flow velocity decreased by 33.83% if the plants were changed from monocrops into clump.AbstrakNilai kekasaran hidrolik adalah nilai yang menggambarkan perkiraan retensi terhadap aliran karena kehilangan energi yang disebabkan oleh gesekan antara saluran dan air. Jenis, kerapatan, ketinggian vegetasi menyebabkan variasi nilai kekasaran hidrolik. Nilai kekasaran hidrolik dapat diamati dengan menggunakan sebuah model fisik yang mewakili kondisi sesungguhnya. Penelitian ini bertujuan mengetahuipengaruh tanaman yang ditanam pada dataran banjir dengan melakukan percobaan dengan model fisik di laboratorium. Penelitian dilakukan dengan melakukan percobaan dan pengamatan di laboratorium pada sebuah model fisik yang mewakili kondisi penampang pada Sungai Barabai di Kalimantan Selatan. Model dirancang dengan skala 1:110, pada dataran banjirnya ditanam tanaman bambu dengan jarak 1.82x 1.82 cm. Diameter tanaman 0.1 dan panjang 8 cm. Model dibuat dalam dua jenis yaitu model dengan tanaman tunggal dan model dengan tanaman rumpun. Model dipadukan dengan saluran terbuka beserta perangkatnya. Hasil penelitian menunjukan adanya pengaruh tanaman terhadap nilai kekasaran hidrolik. Nilai ini ditunjukkan oleh nilai n4 yang meningkat sebesar 69 – 70% apabila tanaman diubah dari tanaman tunggal menjadi tanaman rumpun. Peningkatan ini disebabkan meningkatnya kerapatan tanaman. Selain itu diketahui kecepatan aliran menurun sebesar 2.3 – 1.7% apabila tanaman diubah dari tanaman tunggalmenjadi tanaman rumpun.